High Accurate Automatic School Bell Controller Based On ESP-32 Wi-Fi - Zaghlool Mahmood, Riyadh (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Nowadays, the start and end bells for lessons in most schools are manually operated. Where the timings of operating the bell are inaccurate and depend on the accuracy of the watch of the authorized person or the school for this task, and sometimes the person may forget the time or delay or advance the time of ringing the bell. In this paper, a high accurate school bell controller based on ESP32 and DS3231 Real Time Clock module implemented with using Wi-Fi to correct the system time whenever switched OFF and ON despite of that the accuracy of the DS3231 RTC is +-40 seconds per year with the absence of the Internet. The Bluetooth part of ESP32 is used to configure the system by inserting timetable of the school, the time delay for ringing bell, offset time for the country, and configuring SSID and PASS of the router.